A Case for Collaborative Inquiry in Doctoral Education. Issue 147 (15th September 2015) - Charaniya, Nadira K.; West Walsh, Jane
Abstract : This chapter provides details of a collaborative research journey and makes a case for the inclusion of collaborative inquiry as an accepted doctoral research approach.